La difusión cultural musical de la casa de la cultura ecuatoriana Benjamín Carrión núcleo Zamora Chinchipe, y su incidencia en el desarrollo artístico musical de las agrupaciones musicales del cantón Zamora. Periodo 2012 - 2013 - Narvaez Alba, José Luis (2014)
This research work has been put into effect for the primary purpose of contributing to the strengthening of cultural dissemination of Ecuadorian Culture House " Benjamín Carrión " Zamora Chinchipe core through the artistic development of the musical ensembles of Zamora Canton with conformation Vocal Instrumental Group of the House of Culture through a selection of voices and instrumentalists. To achieve these purposes, plated aim: " To contribute to the musical culture diffusion of Ecuadorian Culture House " Benjamín Carrión " Core Zamora, musical and artistic development of the musical groups of the locality". By employing techniques and procedures, the impact that cultural diffusion for the musical artistic development of Canton was determined. To achieve the objective, a survey was conducted in the institution, in order to ascertain whether the authorities of the House of Culture and members of musical groups known about cultural diffusion and musical artistic development; and interest when providing the same for forming the vocal group - instrumental, the universe under investigation was delimited by applying the technique of population sampling, conforming with 1 director of the House of Culture 10 directors of the musical groups of Canton, 150 members of the musical groups of the canton and five presidents of the districts of the canton, to whom he applied a structured interview guide and questionnaire respectively ; the following specific objectives : " Establish proposals musical training at the House of Culture" Benjamín Carrión " Core Zamora Chinchipe , through seminars , workshops and conferences to disseminate and promote the art of music in the industry. " ; " Select five musicians who integrated the first instrumental vocal group of the House of Culture " Benjamín Carrión " Core Zamora Chinchipe , using the call addressed to the citizens of Canton Zamora. " ; and " Organizing a musical art event in order to present the first instrumental vocal group of the House of Culture " Benjamín Carrión " Core Zamora Chinchipe , it will serve to promote musical culture diffusion of the institution." The proposed guidelines were validated and socialized in a socio- cultural event in the House of Ecuadorian Culture, with the presentation and participation in the group and formed. As the main results, we found that the authorities, teachers and students mostly I favored the realization of the research, enabling the creation of integrated four musicians Instrumental Vocal group : Bolivar Gomez on bass, Diego Chalan Campoverde on piano and vocals, Ronier Cave Salazar on drums and small percussion , Narváez José Luis Alba, lead vocals and director of the group . The main conclusion is the lack of budget and resources for the implementation of materials and tools for the formation of musical groups that contribute to the musical culture diffusion in and out of the town. The recommendation has been taken into account is the charge of spreading awareness Cultural Institution, presidents of the districts , principals and also the members of the musical groups of Canton, on the importance of the development of projects that contribute to the cultural development locality .